1988
DOI: 10.1017/s1323358000022475
|View full text |Cite
|
Sign up to set email alerts
|

Recent Results on SN 1987A

Abstract: A b s t r a c t ! Several critical issues recently raised by observations of SN 1987A are addressed. These include: 1) the evolution of the pre-supernova star, why it was blue, what its composition and core structure were; 2) the detailed isotopic composition of the ejecta; 3) why and to what extent the supernova composition was mixed in velocity space; 4) the interpretation of recently observed infrared lines, especially their profiles and the existence of red-shifted 'wings'; and 5) what has become of the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Neon has also been observed in supernova ejecta (Thieleman et al 1986;Woosley et al 1988). Ne III lines have been identified in the spectrum of solar active region (Thomas & Neupert 1994).…”
Section: Introductionmentioning
confidence: 94%
“…Neon has also been observed in supernova ejecta (Thieleman et al 1986;Woosley et al 1988). Ne III lines have been identified in the spectrum of solar active region (Thomas & Neupert 1994).…”
Section: Introductionmentioning
confidence: 94%
“…Thus you can tell at a glance that the Thielemann et al (1990) model ejected 1.48 Me of 016, 0.228 Mo of Ne 2~ 0.147 MG of Mg 24, and so forth from hydrogen to gallium. By the same token, the Woosley et al (1988) model ejected 1.6 Mo of 016, 0.18 Mo of Ne 2~ 0.096 Mo of Mg 24, and so forth from hydrogen to zinc, when the cut between neutron star and expelled envelope was drawn to give the right amount of Ni s6. Both of these are high C12(e,7)O 16 models of 20Mo stars with 6Mo helium cores at the time of collapse, and initial metallicity about 1/3 solar.…”
Section: Type II Supernovaementioning
confidence: 99%
“…much of the cosmic ray spallation comes from lower energy particles than those directly detected at earth) are probably such that neither serious disagreement or complete confirmation can be claimed for any of them. Table 6 shows the amounts of elements from carbon to copper produced by a Nomoto et al (1984;Thielemann et al 1986) Type Ia supernova and a Woosley et al (1988) Type II. The former ejected 1.32 solar masses of heavy elements, the latter (which is a 20 Mo star model for SN 1987A) 2.67 Mo of heavy elements.…”
Section: The X-processmentioning
confidence: 99%
“…The infrared luminosity continued to decline until day 1050 (Fig. 4) [3] where L. is the SIBL extrapolated to t = 0, and f(t) is the fraction of the y ray energy that can be thermalized in the ejecta;f is unity at outburst and decreases later as the ejecta become optically thin to y rays (20). The obscuring dust directly affects the UBV decline rates (Fig.…”
Section: Evidence For Dust Formation In Sn 1987amentioning
confidence: 99%
“…It seems possible that the condensation of water ice onto the grains could have accelerated their growth after day 700. Woosley et al (20) have shown that mixing in the outer ejecta should produce an oxygen-rich mixture where the condensation of water might be expected. (Fig.…”
Section: Evidence For Dust Formation In Sn 1987amentioning
confidence: 99%